Cohort prospective study of the heart and vessel condition in patients with ischemic heart disease combined with type 2 diabetes - Koshlia, Volodymyr; Piskun, Anastasiia (ScienceRise: Medical Science, 2019)
The article is devoted to the evaluation of peculiarities of cardiac hemodynamics in patients with type 2 diabetes mellitus (type 2 diabetes) in combination with ischemic heart disease (IHD). The main parameters of the function of the heart and structural and functional changes of the common carotid artery (SCA), features of carbohydrate and lipid metabolism have been studied. Aim: To evaluate the peculiarities of cardiac hemomodynamics in patients with type 2 diabetes in combination with IHD and to find correlations with other cardiovascular risk factors in these patients. Materials and methods: 100 patients with IHD were included in the study: patients with type 2 diabetes in combination with coronary heart disease, stable angina pectoris (n=60) – 1 group, 2 groups – patients with coronary heart disease: stable angina pectoris II-III FC without violations of carbohydrate metabolism (n = 40). In the study of patients, the analysis of complaints, cardiological anamnesis, vascular risk factors, objective research, clinical and laboratory and clinical and instrumental research methods were performed, which included ECG, Holter monitoring of ECG, Echo-CG, and vegetative ECG tests. Results: On the basis of the conducted studies we revealed more severe violations of the diastolic function of the left ventricle, increased volumetric parameters of the heart, thickening of the intima-media complex in patients with coronary heart disease on the background of type 2 diabetes. According to the results of vegetative tests, 71.7% of patients in group 1 revealed signs of diabetic autonomic cardiac neuropathy (DANS). Episodes of painless myocardial ischemia (BBIM) in patients in group 1 were twice as likely to occur in group 2 patients (45% of the total number of patients with diabetes mellitus) than in patients without type 2 diabetes (20% of the total number of patients without diabetes type 2). Conclusions: Significant violations of lipid metabolism, significant violations of autonomic innervation, including the sympathetic nervous system, and longer duration of type 2 diabetes (13.2±6.23) years were characteristic for patients with DANS, in combination with BBIM. In patients with type 2 diabetes with DANS signs, an increase in the diameter of the CCA and the thickness of the intima-media complex was observed, indicating a more pronounced atherosclerotic vascular trauma in the central nervous system, and is an independent predictor of acute cardiovascular and cerebrovascular events. The presence of type 2 diabetes in patients with coronary heart disease accelerates the progression of LV remodelling and enhances myocardial dysfunction of the lungs, which is also one of the explanations for the higher risk of cardiac events in patients with coronary artery disease of the concomitant type 2 diabetes. It is advisable for all patients with type 2 diabetes to conduct an ultrasound examination of the heart with an estimate of intima-media thickness, as well as daily ECG monitoring for the early detection of atherosclerosis, episodes of BBIM, and timely treatment